Using H2O2 Bleaching and DTPA Spraying on the Brightness Stability of Beech CMP Pulp Following Accelerated Irradiation Aging - Vaysi, Ramin; Mirshokraie, S.A. (Asian Journal of Chemistry, 2011)
In this research, beech chips were chosen randomly from the chips pile of Mazandaran pulp and Paper Mill in north of Iran and cooked under CMP conditions and pulps were prepared at the yield 85 %. The CMP pulp was separately bleached with hydrogen peroxide and sodium dithionite with and without treating with DTPA. Then 60 g/m2 handsheet were made. A solution of 0.5 % of DTPA was sprayed over a number of handsheets. Then the handsheets were irradiated for, 10, 20, 30 and 40 h and their optical characteristics were measured and compared before and after irradiation using TAPPI standard test methods. The results of this study explored that following irradiation up to 40 h, yellowness, opacity, absorption coefficient, K/S ratio and post colour number increased and brightness decreased. Also complementary bleaching with sodium dithionite improved the optical behaviour of the handsheets. Following DTPA solution spraying on the surface of handsheets brightness, opacity and yellowness in improved and K/S ratio and post colour number is decreased. Among different samples and following optical aging, it was found that in long-term aging, DTPA spray has considerable affect on the stability of brightness and increasing it durability against optical deterioration.